Audit Mutu Atas Penerapan Sistem Manajemen Mutu ISO 9001:2000 Terhadap Kinerja Perusahaan (Studi Kasus PT "X" Palembang) - Dewi Rina (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2009)
Global challenges facing the world can not be avoided either from government or private sector, all parties are required to prepare themselves to survive in the face of these conditions. Along with this globalization, standardization of management has become a major issue, more specifically, the standardization of quality standards. For that, a government agency or private well need to prepare a framework of quality systems towards a desired institution in accordance with the goals or objectives set by the end of these institutions, in the sense that the goals or objectives of quality of an institution capable of achieving compliance with the expected desire of customers or partner institutions.Responding to the issues mentioned above, one of the quality standard has been recognized many flying businesses is growing in developed countries and even in developing countries was first issued in 1947 by the International Organization for Standardization (ISO) is a federation of national standards bodies throughout world who come from 100 countries, ISO's mission is to enhance the development of standardization and related activities in the world to facilitate international exchange view of goods and services and to developing cooperation in the field of intellectual activity, science, engineering and economics. ISO's work in an international agreement which published as International Standards, ie ISO 9001: 2000 as an international standard for quality management systemsKeyword : Effectivity, Quality Management System